Emission factors from residential combustion appliances burning Portuguese biomass fuels - Fernandes, A. P.; Alves, C. A.; Goncalves, C.; Tarelho, L.; Pio, C.; Schimdl, C.; Bauer, H. (Journal of Environmental Monitoring, 2011)
Smoke from residential wood burning has been identified as a major contributor to air pollution, motivating detailed emission measurements under controlled conditions. A series of experiments were performed to compare the emission levels from two types of wood-stoves to those of fireplaces. Eight types of biomass were burned in the laboratory: wood from seven species of trees grown in the Portuguese forest (Pinus pinaster, Eucalyptus globulus, Quercus suber, Acacia longifolia, Quercus faginea, Olea europaea and Quercus ilex rotundifolia) and briquettes produced from forest biomass waste. Average emission factors were in the ranges 27.5-99.2 g CO kg-1, 552-1660 g CO2 kg-1, 0.66-1.34 g NO kg-1, and 0.82-4.94 g hydrocarbons kg-1 of biomass burned (dry basis). Average particle emission factors varied between 1.12 and 20.06 g kg-1 biomass burned (dry basis), with higher burn rates producing significantly less particle mass per kg wood burned than the low burn rates. Particle mass emission factors from wood-stoves were lower than those from the fireplace. The average emission factors for organic and elemental carbon were in the intervals 0.24-10.1 and 0.18-0.68 g kg-1 biomass burned (dry basis), respectively. The elemental carbon content of particles emitted from the energy-efficient "chimney type" logwood stove was substantially higher than in the conventional cast iron stove and fireplace, whereas the opposite was observed for the organic carbon fraction. Pinus pinaster, the only softwood species among all, was the biofuel with the lowest emissions of particles, CO, NO and hydrocarbons.
The following values have no corresponding Zotero field: publisher: The Royal Society of Chemistry
Keywords: Biomass combustion; Emission factors; Wood stove (voyant)

Assessment and up-scaling of CO2 exchange by patches of the herbaceous vegetation mosaic in a Portuguese cork oak woodland - Li, Yue-Lin; Tenhunen, J.; Mirzaei, H.; Hussain, M. Z.; Siebicke, L.; Foken, T.; Otieno, D.; Schmidt, M.; Ribeiro, N.; Aires, L.; Pio, C.; Banza, J.; et al. (Agricultural and Forest Meteorology, 2008)
Long-term eddy covariance measurements over a montado oak woodland in southern Portugal have documented a vulnerability to predicted decreases in springtime rainfall, since water availability during spring limits annual CO2 gain, the growth of fodder for animals, and the production of cork by Quercus suber. The current study examined CO2 exchange of three different herbaceous vegetation components distributed over montado landscapes and within the footprint of long-term landscape eddy covariance monitoring studies. Simultaneous measurements with eddy covariance at two sites and with manually operated chambers at multiple locations revealed that slow drainage of shallow basins, the onset of drying at higher sites and a high release of CO2 below tree canopies signiﬁcantly inﬂuenced the overall course of montado ecosystem gas exchange during the spring. Hyperbolic light response models were employed to up-scale and compare herbaceous gas exchange with landscape net ecosystem CO2 ﬂux. The up-scaling demonstrates the importance of the herbaceous understory in determining annual carbon balance of the montado and suggests a relatively small additional CO2 uptake by the tree canopies and boles, i.e., by the aboveground tree compartment, during springtime. Annual ﬂux totals obtained during the extremely dry year 2005 and a normal precipitation year 2006 for the oak woodland and a nearby grassland were essentially the same, indicating that both ecosystems similarly exploit available resources. Based on comparisons with additional temperate grasslands, we can visualize the montado herbaceous cover as a typical European grassland canopy, but where temperature ﬂuctuations in winter control uptake, and where total production depends on springtime rainfall as it controls phenological events and eventually dieback of the vegetation. On the other hand, tree canopies remain active longer during late spring and early summer, modifying the montado response from that of grassland. Uncertainties in ﬂux estimates via both chamber and eddy covariance methodologies currently prevent a full understanding of vegetation/atmosphere coupling, of the recycling of CO2 between the understory communities and trees, and of relationships between exchange rates of individual components of the vegetation mosaic and overall carbon and water balances in montado landscapes.
Keywords: Herbaceous vegetation; Light response model; montado; net ecosystem exchange; Oak woodland; up-scaling